2003
DOI: 10.1523/jneurosci.23-23-08254.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Social Memory, Hypothalamic-Pituitary-Adrenal Axis, and Brain Asymmetry by Neonatal Novelty Exposure

Abstract: Although corticosterone (a stress hormone) is known to influence social behavior and memory processes, little has been explored concerning its modulatory role in social recognition. In rats, social recognition memory for conspecifics typically lasts <2 hr when evaluated using a habituation paradigm. Using neonatal novelty exposure, a brief and transient early life stimulation method known to produce long-lasting changes in the hypothalamic-pituitary-adrenal axis, we found that social recognition memory was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 71 publications
7
56
0
1
Order By: Relevance
“…Without the control of GR by LRF, GR-mediated feedback inhibition of HPA axis stimulation by stress may be missing, leading to hyperactivity. Since chronic stimulation of the HPA axis is known to impair social recognition performance (58), the observed impairment of LRF Ϫ/Ϫ female mice, as shown by the social recognition test, implies prolonged HPA axis activity, possibly due to the misregulation of GR. It should be noted that although the hyperactivity observed in PRL Ϫ/Ϫ mice may contribute to the maternal behavioral deficiency, it is unlikely the cause of the defect as hyperactivity is not necessarily linked to poor maternal responses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Without the control of GR by LRF, GR-mediated feedback inhibition of HPA axis stimulation by stress may be missing, leading to hyperactivity. Since chronic stimulation of the HPA axis is known to impair social recognition performance (58), the observed impairment of LRF Ϫ/Ϫ female mice, as shown by the social recognition test, implies prolonged HPA axis activity, possibly due to the misregulation of GR. It should be noted that although the hyperactivity observed in PRL Ϫ/Ϫ mice may contribute to the maternal behavioral deficiency, it is unlikely the cause of the defect as hyperactivity is not necessarily linked to poor maternal responses (42).…”
Section: Discussionmentioning
confidence: 99%
“…During PND 1-21, the neonatal novelty exposure procedure (Fig. 1 B) was carried out in the animal housing room and involved the novel pups spending 3 min away from the familiarity of their home cage and their matched control siblings remaining in the home cage [for details of the method, see Tang (2001) and Tang et al (2003Tang et al ( , 2006]. This procedure is in contrast to the commonly used neonatal handling designs (Levine, 1957(Levine, , 1960Denenberg, 1964) that use a between-litter design in which the nonhandled litters remain entirely undisturbed and the handled litters experience a combination of at least four manipulations: (1) "handling" of experimental animals by the experimenter; (2) separating the neonates from their mother; (3) increasing the mother's stress by separating her from her pups; and (4) exposing the neonates to an unfamiliar environment, i.e., novelty.…”
Section: Methodsmentioning
confidence: 99%
“…The hippocampus, a key brain structure underlying spatial learning (Morris et al, 1982;Sutherland et al, 1982), is both a major target of the stress hormone corticosterone (CORT), an end product of the HPA axis, and one of the major driving forces that provide input to the HPA axis (McEwen and Sapolsky, 1995;de Kloet et al, 1998). Early-life stimulation and differences in maternal characteristics both result in long-lasting changes in the HPA axis and enhancement in spatial learning (Meaney et al, 1988;Catalani et al, 1993Catalani et al, , 2000Casolini et al, 1997;Liu et al, 1997;Tang, 2001;Tang et al, 2003Tang et al, , 2006Akers et al, 2008). What remains controversial is the relative contribution of the neonatal stimulation itself and maternal influence toward the programming of the adult function (Denenberg, 1999;Pryce and Feldon, 2003;Macrì and Würbel, 2006;Parker et al, 2006;Tang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that neonatal isolation has immediate effects on various stress-responsive systems, since plasma corticosterone levels are significantly increased within 30 min of isolation (McCormick et al, 1998), and that stress and concomitant corticosterone secretion facilitates mesolimbic dopaminergic activity (McCormick et al, 2002;Pani et al, 2000). Given that stress clearly affects social behavior, and that early life experience affects an individual's stress response (Tang et al, 2003), it is possible that neonatal surgery impairs the development of social skills. These findings appear to be incongruent with the stress-hyporesponsive period in rodents (pd 4-14), where the adrenal response to stress is minimal (Levine, 2001;Schmidt et al, 2002).…”
Section: Social Behavior and Cpp For Social Contactmentioning
confidence: 99%